Tratamento do digestato oriundo da digestão anaeróbia de efluente da suinocultura em uma unidade piloto do reator nitrammox - Venturin, Bruno (2022)
The swine production chain is one of the most relevant from Brazil's economic point of view. The farming of pigs in a confined manner and with high animal density reduced production costs and improved sanitary control; however, much waste is generated. Therefore, anaerobic digestion is among the most used technologies to manage such waste. This process is widely applied in the country to reduce the organic matter present in the waste of these animals. Despite the relative efficiency in removing organic matter, significant concentrations of ammoniacal nitrogen and organic carbon remain in the digestate. Among the processes for removing this nitrogen, partial nitritation associated with anaerobic oxidation of ammonia (anammox) and denitrification provide higher efficiencies and lower costs for wastewater treatment, especially those with high concentrations of ammonia nitrogen and residual organic matter. There are still many challenges related to the applicability of such a process in swine production farms after treating waste in digesters. Therefore, the present work aimed to study the effect of organic carbon in swine digestate on anammox bacteria (BOAnA), evaluating processes for the pre-treatment of these digestates and subsequent applicability in a deammonification reactor for digestate treatment. The experiments were conducted on a bench scale, with batch feeding, and later in a pilot reactor using the NITRAMMOX® process, continuously operating with pre-treated swine manure. The choice for anaerobic pre-treatment, carried out by a system containing decanters and an anaerobic reactor, proved to be adequate for preparing the digestate operating with the hydraulic retention time of up to 1 day, without instability in the concentration of organic matter. After removing 65% of the organic matter, the nitrogen removal process stabilized; it occurs until a concentration of approximately 100 mg L-1 of total organic carbon is not exceeded. The NITRAMMOX® process, operating on a pilot scale, again proved capable of removing nitrogenous compounds from swine manure. The process presented stable and robust characteristics to work with nitrogen loads higher than conventional biological processes. Swine manure was treated according to the applied nitrogen load up to 2 gN L-1 d-1. Nitrogen removal efficiencies averaged 80% when the process was stable; a theoretical doubling time of 6 d was estimated for the BOAnA.